Whisker-reinforced anti-cracking magnesium phosphate cement anticorrosive coating, preparation method and application thereof

CN122465409BActive Publication Date: 2026-10-13HUNAN UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610969246.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-01
Publication Date
2026-10-13
Estimated Expiration
2046-07-01

AI Technical Summary

Technical Problem

[0009]与现有以疏水或致密化为主的改性体系相比,本发明优先解决裂纹扩展导致的防护失效问题,通过维持涂层结构完整性和界面稳定性,实现长期耐蚀性能提升

Benefits of technology

(1)显著提高涂层断裂韧性与抗裂能力:本发明通过引入高长径比晶须,在MPC基体内部形成微尺度桥联增强网络。当裂纹扩展时,晶须能够通过裂纹桥联、裂纹偏转及裂纹钉扎等机制耗散断裂能量,抑制裂纹贯通,从而显著提高涂层的断裂韧性和抗裂稳定性。相比未增韧MPC涂层,本发明涂层在干湿循环和温度变化条件下不易产生贯通裂纹和界面脱粘。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122465409B_ABST
    Figure CN122465409B_ABST
Patent Text Reader

Abstract

The application discloses a kind of whisker toughening anti-crack magnesium phosphate cement anticorrosion coating and its preparation method and application, belong to building engineering material and anticorrosion technical field.Aiming at the problem that existing magnesium phosphate cement coating is big, easily cracking, resulting in coating denseness drop, long-acting anticorrosion durability is insufficient, the application constructs a kind of " whisker toughening-nanometer densification-hydrophobic barrier " synergistic protection system.Coating includes wollastonite whisker, nanometer silicon dioxide and pretreatment polydimethylsiloxane.Wollastonite whisker inhibits crack propagation by bridging, deflection and pinning effect;Nanometer silicon dioxide refines pore structure;PDMS forms hydrophobic network.Three synergistic effects significantly improve the bonding strength, electrochemical impedance modulus and anti-cracking performance of the coating under seawater immersion, wide temperature range and dry-wet cycle.The coating of the application is suitable for long-acting corrosion protection of steel structures and reinforced concrete components in marine engineering, port and wharf.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials and corrosion protection technology, specifically relating to a whisker-toughened and crack-resistant magnesium phosphate cement anti-corrosion coating, its preparation method and application, and particularly to a magnesium phosphate cement anti-corrosion coating that improves long-term service performance through whisker toughening, nano-densification and hydrophobic modification. Background Technology

[0002] Steel structures, due to their advantages of high strength, convenient construction, and high degree of industrialization, are widely used in major engineering facilities such as offshore platforms, cross-sea bridges, port terminals, and storage tank pipelines. However, the marine environment is characterized by high salinity, high humidity, abundant dissolved oxygen, and large temperature fluctuations. When steel is exposed for extended periods, it is highly susceptible to various failure modes, including uniform corrosion, pitting corrosion, crevice corrosion, and stress corrosion cracking. This leads to a significant reduction in load-bearing capacity and stiffness, and substantially increases maintenance costs and downtime losses. To extend the service life of steel structures, the common practice in engineering is to coat the steel surface with organic or inorganic anti-corrosion coatings to block corrosive media and inhibit electrochemical reactions.

[0003] Traditional organic anti-corrosion coatings, such as epoxy resins, polyurethanes, zinc-rich epoxy coatings, and zinc-rich geopolymer coatings, have been widely used in marine engineering due to their excellent density and resistance to media penetration. However, these coatings, which mostly use petroleum-based polymers or zinc-rich pigments as the main film-forming substances and anti-corrosion components, generally suffer from the following problems: First, the resin matrix is ​​prone to brittleness, powdering, and debonding under UV aging, temperature cycling, and stress, leading to a decline in long-term protective performance; second, zinc-rich systems are environmentally unfriendly, have high carbon emissions, and require strict pretreatment of the substrate surface; third, high-solids or solvent-based formulations often come with volatile organic compound (VOC) emissions and combustion risks, which are not conducive to green and low-carbon development requirements. Related studies have shown that the unit carbon emissions of typical polyurethane, epoxy resin, and waterborne epoxy modified coatings are mostly between 1900-4000 kg / t, significantly higher than those of inorganic magnesium phosphate cement-based coating systems.

[0004] Magnesium phosphate cement (MPC) possesses characteristics such as early strength, high adhesion, high fire resistance, and good compatibility with steel substrates, making it a promising candidate for application in steel structures and reinforced concrete protection. However, MPC itself is a typical brittle cementitious material, which is prone to developing microcracks due to temperature fluctuations, wet-dry cycles, and salt erosion during long-term service in marine environments. These microcracks can further develop into through cracks, allowing corrosive media to rapidly penetrate the steel-coating interface, leading to interface debonding and protective failure.

[0005] In recent years, to improve the durability of magnesium phosphate cement coatings, researchers have employed methods such as organosilicon modification to enhance their corrosion resistance. Among these methods, polydimethylsiloxane (PDMS) can reduce the surface energy of the material and increase the hydrophobicity of the coating, thereby reducing the penetration of moisture and chloride ions into the coating interior and improving the corrosion resistance of magnesium phosphate cement coatings to some extent. However, existing PDMS-modified magnesium phosphate cement coatings still face the potential risk of developing microcracks or even penetrating cracks under long-term marine environments, temperature changes, and wet-dry cycles, leading to debonding of the steel-coating interface and a decline in protective performance. Therefore, simply relying on hydrophobic or densification mechanisms is insufficient to fundamentally inhibit crack propagation and improve system toughness, and is inadequate to meet the requirements of marine engineering structures for long-life protective materials.

[0006] Whiskers possess a high aspect ratio, good chemical stability, and excellent interfacial compatibility with cement-based materials, enabling them to form a microscale reinforcing framework within the matrix. During crack propagation, whiskers dissipate fracture energy through mechanisms such as bridging, crack deflection, and crack pinning, effectively improving the fracture toughness and crack resistance of the material. Simultaneously, whiskers can alleviate interfacial stress concentration caused by temperature changes and wet-dry cycles, maintaining the microstructural stability of the coating.

[0007] However, existing literature and patents contain limited research on the application of whiskers in magnesium phosphate cement marine anti-corrosion coatings, particularly lacking systematic studies on the multi-scale synergistic mechanism of "whisker toughening—nano-densification—PDMS hydrophobic barrier." Therefore, it is necessary to develop a whisker-toughened MPC anti-corrosion coating system that combines high toughness, high density, and long-term corrosion resistance to meet the long-term service requirements of steel structures and reinforced concrete components in marine environments. Summary of the Invention

[0008] The technical problem to be solved by this invention is to overcome the shortcomings and defects existing in the above-mentioned background technology and provide a crack-resistant, toughening, and anti-corrosion coating system based on crack control mechanism. By introducing wollastonite whiskers into the magnesium phosphate cement matrix to construct a bridging and reinforcing network, the crack bridging, crack deflection, and crack pinning effects of the whiskers are utilized to inhibit the initiation and propagation of microcracks; at the same time, combined with the pore structure refinement effect of nano-silica and the hydrophobic barrier effect constructed by PDMS, a multi-scale synergistic protection mechanism of "crack resistance and toughening - structural density - hydrophobic barrier" is formed.

[0009] Compared with existing modification systems that are mainly based on hydrophobicity or densification, this invention prioritizes solving the problem of protection failure caused by crack propagation, and achieves long-term corrosion resistance improvement by maintaining the integrity of the coating structure and the stability of the interface.

[0010] To solve the above-mentioned technical problems, the technical solution proposed by this invention is as follows: A whisker-reinforced, crack-resistant magnesium phosphate cement anti-corrosion coating, based on 100 parts by weight of reburned magnesium oxide, comprises the following components: 28-50 parts by weight of phosphate curing agent; 3-10 parts by weight of borax; 1-5 parts by weight of disodium hydrogen phosphate dodecahydrate; Sodium hexametaphosphate, 0.2-0.5 parts by weight; 2-15 parts by weight of wollastonite whiskers; Pretreatment of polydimethylsiloxane: 1.5-12 parts by weight; 1-6 parts by weight of nano-silica; And mixing water; Wherein, the phosphate curing agent is potassium dihydrogen phosphate, and the mixing water satisfies a water-to-binder ratio of 0.13 to 0.17; The water-to-binder ratio refers to the ratio of the mass of mixing water to the total mass of all solid components, which include calcined magnesium oxide, phosphate curing agent, borax, disodium hydrogen phosphate dodecahydrate, sodium hexametaphosphate, wollastonite whiskers, and nano-silica. The pretreated polydimethylsiloxane is a liquid organic phase and is not included in the solid components.

[0011] Furthermore, the wollastonite whiskers have an aspect ratio of 10 to 40 and an average length of 20 to 200 μm.

[0012] Furthermore, the average length of the wollastonite whiskers is 50~150μm.

[0013] Furthermore, the pretreated polydimethylsiloxane is obtained by premixing polydimethylsiloxane, tetraethoxysilane and dibutyltin dilaurate in a mass ratio of 100:(5~15):(0.5~2).

[0014] Furthermore, the average particle size of the nano-silica is 10~30nm, and the specific surface area is not less than 200m². 2 / g.

[0015] Furthermore, the amount of wollastonite whiskers is 4-10 parts by weight; and / or The pretreated polydimethylsiloxane dosage is 4-8 parts by weight; and / or The amount of nano-silica doped is 2-4 parts by weight; and / or The water-to-binder ratio is 0.14 to 0.16.

[0016] Furthermore, the amount of wollastonite whiskers is 6 parts by mass; The amount of pretreated polydimethylsiloxane is 6 parts by mass; The amount of nano-silica doped is 4 parts by mass; The water-to-binder ratio is 0.15.

[0017] The present invention also provides a method for preparing the whisker-reinforced, crack-resistant magnesium phosphate cement anticorrosion coating, comprising the following steps: (1) Add nano-silica to part of the mixing water and disperse to obtain a nano-silica aqueous dispersion; (2) Mix the pretreated polydimethylsiloxane, phosphate curing agent, borax, disodium hydrogen phosphate dodecahydrate, sodium hexametaphosphate and part of the nano silica aqueous dispersion evenly to obtain a premixed solution; (3) Add calcined magnesium oxide, wollastonite whiskers and the remaining nano-silica aqueous dispersion to the premixed liquid and stir to obtain a coating slurry; (4) Apply the coating paste to the surface of the substrate and cure it.

[0018] Furthermore, in step (3), the mixture is first stirred at a low speed of 150~300r / min for 20~60s, and then stirred at a high speed of 400~600r / min for 2~5min.

[0019] The present invention also provides the application of the whisker-toughened and crack-resistant magnesium phosphate cement anticorrosion coating in the surface anticorrosion protection of steel structures, reinforced concrete structures, marine engineering structures, underground sewage pipes or municipal infrastructure.

[0020] Compared with the prior art, the advantages of this invention are as follows: (1) Significantly improves the fracture toughness and crack resistance of the coating: This invention introduces high aspect ratio whiskers to form a microscale bridging reinforcement network within the MPC matrix. When cracks propagate, the whiskers can dissipate fracture energy through mechanisms such as crack bridging, crack deflection, and crack pinning, inhibiting crack propagation and thus significantly improving the fracture toughness and crack resistance of the coating. Compared with untoughened MPC coatings, the coating of this invention is less prone to penetrating cracks and interface debonding under wet-dry cycling and temperature change conditions.

[0021] (2) Balancing high density and mechanical stability: Nano-SiO2 can fill the capillaries and microcracks in the MPC matrix and act as a nucleation core to promote the formation of hydration products, thereby effectively refining the pore structure and improving the density of the matrix. Wollastonite whiskers and nano-SiO2 together construct a multi-scale reinforcement structure of "micron-level reinforcing framework + nano-level filling network", which improves crack resistance while maintaining high mechanical strength and interfacial bonding performance.

[0022] (3) Significantly improves long-term corrosion resistance: PDMS forms a low surface energy hydrophobic network inside the substrate, which can effectively reduce the penetration rate of seawater and chloride ions into the coating; nano-SiO2 increases the ion diffusion resistance; and wollastonite whiskers reduce the penetration channels of corrosive media by inhibiting crack propagation. Under the synergistic effect of the three, the coating can still maintain a high electrochemical impedance modulus and a low corrosion current density under long-term seawater immersion and wet-dry cycle conditions.

[0023] (4) Improve interface stability and delay structural degradation: Whiskers can alleviate interface stress concentration caused by wet-dry cycles and temperature changes, and reduce the risk of cracking at the steel-coating interface; at the same time, nano-SiO2 and MPC hydration products together form a stable cemented structure, and PDMS reduces the probability of hydration products being directly exposed to the corrosive medium, thereby effectively delaying the K-struvite phase transformation and pore structure coarsening, and improving the long-term service stability of the coating.

[0024] (5) The process is simple and has good engineering applicability: The present invention can be prepared by conventional stirring, dispersing and scraping process, without the need for complicated equipment or high temperature treatment. The raw materials are widely available and the construction is convenient. It is suitable for long-term corrosion protection of marine engineering, port terminals, cross-sea bridges and reinforced concrete structures. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort, wherein: Figure 1 Electrochemical impedance spectroscopy (EIS) spectra of the coating prepared in Example 2 of this invention and Comparative Example 4 (PW) after immersion in artificial seawater at 20°C for 90 days.

[0026] Figure 2 This is a comparison chart of the residual bonding strength of the coating in Example 2 and Comparative Example 2 (P) after being immersed in artificial seawater at different temperatures for 90 days.

[0027] Figure 3 The corrosion current density (Icorr) of the coating of Example 2 and Comparative Examples 1 (REF), 2 (P), 3 (PNS), and 4 (PW) after immersion in artificial seawater at 20°C for 90 days is shown in the figure.

[0028] Figure 4 The backscattered electron (BSE) pattern of the coating-steel substrate interface after 28 wet-dry cycles is shown for Comparative Example 1 (REF).

[0029] Figure 5This is a backscattered scanning electron (BSE) image of the coating-steel substrate interface after the coating of Embodiment 2 of the present invention has undergone 28 dry and wet cycles.

[0030] Figure 6 This is a scanning electron microscope (SEM) image of the coating in Embodiment 2 of the present invention after 28 wet-dry cycles. Detailed Implementation

[0031] The technical solutions of the present invention will now be clearly and completely described with reference to the accompanying drawings in this embodiment. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0032] The technical solutions of the present invention will now be clearly and completely described with reference to the accompanying drawings of this embodiment. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.

[0033] Example 1: Preparation and performance testing of whisker-reinforced, crack-resistant magnesium phosphate cement anticorrosion coating In this embodiment, a whisker-reinforced, crack-resistant magnesium phosphate cement anticorrosion coating was prepared according to the preferred formulation of the present invention, and its crack resistance, interfacial adhesion, and corrosion resistance were tested.

[0034] 1. Raw materials and proportions; Calcined magnesium oxide (MgO): 100 parts; potassium dihydrogen phosphate (PDP): 40 parts; borax: 6 parts; disodium hydrogen phosphate dodecahydrate: 2.5 parts; sodium hexametaphosphate: 0.3 parts; wollastonite whiskers: 6 parts; pretreated PDMS: 6 parts; nano-SiO2: 4 parts; mixing water: total water-to-binder ratio 0.15. Among these, the average length of the wollastonite whiskers is approximately 100 μm, and the aspect ratio is approximately 20; the average particle size of the nano-SiO2 is approximately 20 nm; the pretreated PDMS was prepared by premixing PDMS, TEOS, and dibutyltin dilaurate in a mass ratio of 100:10:1.

[0035] 2. Preparation method; (1) Dispersion of nano-SiO2: Add nano-SiO2 to about one-third of the total mixing water and disperse it by ultrasonication for 15 minutes to obtain a uniform dispersion.

[0036] (2) Liquid phase premixing: Potassium dihydrogen phosphate, borax, disodium hydrogen phosphate dodecahydrate and sodium hexametaphosphate were added to the remaining mixing water and stirred until completely dissolved. Then, pretreated PDMS and part of nano-SiO2 dispersion were added and stirred for another 30 seconds to obtain the premixed solution.

[0037] (3) Preparation of slurry: Add calcined magnesium oxide, wollastonite whiskers and remaining nano-SiO2 dispersion to the above premixed liquid. Stir at 200 r / min for 30 s, then stir at 500 r / min for 210 s to obtain a uniformly coated slurry.

[0038] (4) Coating and curing: Apply by scraping, and control the wet film thickness to about 500 μm. After coating, cure at 20±2℃ and 65±5% relative humidity for 48 hours.

[0039] 3. Performance test results; (1) Crack resistance: During the artificial seawater dry-wet cycle, wollastonite whiskers were uniformly distributed within the MPC matrix, forming a continuous reinforcing network with the hydration products. SEM observation revealed that the whiskers could form bridging structures across the cracks and induce crack deflection and bifurcation, thereby reducing the crack propagation rate. After 28 artificial seawater dry-wet cycles, no obvious through cracks were found on the coating surface.

[0040] (2) Adhesion performance: The initial adhesion strength of the coating of the present invention is 5.3±0.2MPa. After being soaked in artificial seawater for 90 days, the adhesion strength retention rate exceeds 80%.

[0041] (3) Corrosion resistance: After being immersed in artificial seawater for 90 days, the coating still maintains a high electrochemical impedance modulus and a low corrosion current density.

[0042] (4) Microstructure: Nano-SiO2 reduces the proportion of macropores and improves the density of the matrix. A good interfacial bond is formed between whiskers and MPC hydration products. PDMS is uniformly distributed in the pore walls and interfacial regions, forming a hydrophobic barrier structure.

[0043] Example 2: Long-term durability verification under wide temperature range and wet / dry cycling conditions Coated specimens were prepared using the formulation and process described in Example 1. They were then immersed in artificial seawater at 5°C, 20°C, 40°C, and 60°C for 90 days, respectively. Figure 2 As shown, the coatings maintained high bonding strength and interface stability under different temperature conditions. After immersion in artificial seawater at 60°C for 90 days, the bonding strength retention rate between Example 2 and the steel plate still exceeded 80%.

[0044] Coated specimens were prepared using the formulation and process described in Example 1. Artificial seawater wet-dry cycle tests were conducted, with the following cycle regime: seawater immersion for 12 hours, followed by drying at 40°C for 11 hours, constituting one cycle. Figure 5 As shown, according to the BSE results, after 28 cycles, the coating still maintained its intact structure, and no obvious interface debonding was observed. Figure 6 As shown, SEM observations indicate that the whisker bridging structure remains intact, and the nanoparticles fill the pores of the coating matrix. At the same time, the nanoparticles are encapsulated by PDMS, forming a micro-nano composite rough structure, which enhances the hydrophobic properties of the coating and can effectively block the intrusion of seawater solutions.

[0045] Comparative Example 1 (REF): The formulation was the same as in Example 1, but without the addition of wollastonite whiskers, PDMS, and nano-SiO2. Test results showed that the REF coating was prone to developing through-cracks during wet-dry cycling, and exhibited significant interfacial debonding. Figure 4 As shown, after 28 wet-dry cycles, numerous through cracks and significant debonding appeared at the REF coating-steel substrate interface.

[0046] Comparative Example 2 (P): Six parts of pretreated PDMS were added to the REF coating. The results showed that the hydrophobic properties of the coating were significantly improved, but after immersion in seawater at different temperatures for 90 days, the adhesion strength between the P coating and the steel plate was lower than that of Example 2. Figure 2 As shown.

[0047] Comparative Example 3 (PNS): Four parts of nano-SiO2 were further added to the P coating. The results showed that the matrix density was improved and the corrosion resistance was further enhanced. However, after long-term wet and dry cycling, its electrochemical impedance modulus was lower than that of Example 2.

[0048] Comparative Example 4 (PW): Six parts of wollastonite whiskers and six parts of pretreated PDMS were added to the REF base, without the addition of nano-SiO2. The results showed that the whisker bridging effect effectively inhibited crack propagation, and PDMS imparted certain hydrophobic properties to the coating, thus significantly improving crack resistance compared to Comparative Example 2 (P). However, due to the lack of nano-SiO2 to fill and refine the pore structure, many capillary pores still existed inside the matrix. During long-term seawater immersion and wet-dry cycles, corrosive media could still penetrate along the pores, resulting in corrosion current densities higher than those in Example 2 of this invention. Figure 1 As shown.

[0049] Electrochemical performance comparison: such as Figure 3 As shown, after immersion in artificial seawater at 20°C for 90 days, the corrosion current density of the coating in Example 2 of this invention was significantly lower than that of all comparative examples, indicating that its corrosion resistance was significantly improved.

[0050] Comparison of the results from the examples and comparative examples shows that PDMS mainly provides hydrophobic barrier properties, nano-SiO2 mainly refines the pore structure and improves matrix density through filling and nucleation effects, and wollastonite whiskers mainly improve material toughness and interfacial stability through crack bridging, crack deflection, and crack pinning. When any component is missing from the system, the coating exhibits a significant decrease in long-term corrosion resistance, crack resistance, or structural density; only with the synergistic effect of all three components can a multi-scale protective effect of crack resistance and toughening, structural density, and hydrophobic barrier be achieved simultaneously, thereby significantly improving the long-term service performance of magnesium phosphate cement-based anti-corrosion coatings.

[0051] The embodiments of the present invention have been described above with reference to the accompanying drawings. However, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of the present invention without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of the present invention.

Claims

1. A whisker-reinforced, crack-resistant magnesium phosphate cement anticorrosion coating, characterized in that, Based on 100 parts by weight of reburned magnesium oxide, it comprises the following components: 28-50 parts by weight of phosphate curing agent; 3-10 parts by weight of borax; 1-5 parts by weight of disodium hydrogen phosphate dodecahydrate; Sodium hexametaphosphate, 0.2-0.5 parts by weight; Six parts by mass of wollastonite whiskers with an aspect ratio of 10 to 40 and an average length of 50 to 150 μm; Six parts by mass of pretreated polydimethylsiloxane were obtained by premixing polydimethylsiloxane, tetraethoxysilane and dibutyltin dilaurate in a mass ratio of 100:(5~15):(0.5~2). Average particle size of 10~30nm and specific surface area of ​​not less than 200m² 2 / g of nano-silica, 4 parts by weight; And mixing water; Wherein, the phosphate curing agent is potassium dihydrogen phosphate, and the mixing water satisfies a water-to-binder ratio of 0.15; The water-to-binder ratio refers to the ratio of the mass of mixing water to the total mass of all solid components, which include calcined magnesium oxide, phosphate curing agent, borax, disodium hydrogen phosphate dodecahydrate, sodium hexametaphosphate, wollastonite whiskers, and nano-silica.

2. A method for preparing the whisker-reinforced, crack-resistant magnesium phosphate cement anticorrosion coating as described in claim 1, characterized in that, Includes the following steps: (1) Add nano-silica to part of the mixing water and disperse by ultrasonication to obtain a nano-silica aqueous dispersion; (2) Mix the pretreated polydimethylsiloxane, phosphate curing agent, borax, disodium hydrogen phosphate dodecahydrate, sodium hexametaphosphate and part of the nano silica aqueous dispersion evenly to obtain a premixed solution; (3) Add calcined magnesium oxide, wollastonite whiskers and the remaining nano-silica aqueous dispersion to the premixed liquid and stir to obtain a coating slurry; (4) Apply the coating paste to the surface of the substrate and cure it.

3. The method according to claim 2, characterized in that, In step (3), first stir at a low speed of 150~300r / min for 20~60s, then stir at a high speed of 400~600r / min for 2~5min.

4. The application of the whisker-toughened and crack-resistant magnesium phosphate cement anticorrosion coating of claim 1 in the anticorrosion protection of steel structures, reinforced concrete structures, marine engineering structures or underground sewage pipelines.

Citation Information

Patent Citations

  • Pavement patching material with high early strength and toughness and preparation method thereof

    CN121135356A